KEBANGKITAN LEMBAGA PENDIDIKAN ISLAM NON-FORMAL PUSAT TAREKAT: KEBANGKITAN LEMBAGA PENDIDIKAN ISLAM NON-FORMAL PUSAT TAREKAT - Muhtadi, Faiz; Amin, Alfauzan; Saepudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the resurgence of non-formal Islamic educational institutions rooted in Sufi orders (tarekat) in Indonesia, a phenomenon closely linked to the growing spiritual needs of modern society. Rapid modernization, psychological pressure, and increasing mental health challenges have resulted in a renewed search for spiritual guidance, making tarekat-based education an attractive alternative to formal schooling. The purpose of this study is to analyze the factors driving the revival of tarekat institutions, the transformations occurring within their educational practices, and their relevance to character education in contemporary contexts. Using a qualitative descriptive approach, data were collected through participant observations of ritual and educational activities such as dhikr gatherings, suluk, halaqah sessions, and kitab studies; in-depth interviews with mursyid, teachers, senior disciples, and community members; and documentation of institutional records. Data were analyzed through interactive stages of reduction, display, and conclusion drawing. The findings reveal that tarekat institutions have evolved into structured centers of non-formal education that integrate cognitive, affective, and psychomotor learning. They provide holistic character formation, foster social cohesion, strengthen moral-spiritual development, and adapt effectively to digital technology for wider outreach. Furthermore, various case studies indicate increasing public participation in tarekat activities, particularly among youth. The study concludes that tarekat- based education remains highly relevant for strengthening spirituality, promoting moderate Islamic values, and enhancing character education in modern Indonesian society.